Imageries of Self: Guilty Plea Statements in Sexual Violence Cases at the ICTY - Houge, Anette Bringedal (International criminal justice review, 2023)
Focusing on the guilty plea statements in sex crimes cases at the International Criminal Tribunal for the former Yugoslavia, this article investigates the ways that defendants re-present themselves, their agencies, and their offenses in response to the legal framework within which they talk. While their acts are at the core of international criminal justice (ICJ), defendants are more often spectators than participants when their guilt is negotiated and judged. They have for the most part also been absent in research on ICJ. As defendants’ voices are rarely heard during proceedings, their guilty plea statements produce rare access to war criminal’s staging of self and individual agency. At international criminal tribunals, defendants have wide audiences beyond the courtroom, and when they do speak, their stories potentially influence not only the court proceedings but also wider cultural and societal narratives about wartime agency and sexual violence. After identifying a guilty plea script, this article draws attention to a consistent and intriguing silencing of sexual crimes in the past and to how the defendants’ imageries of present and future selves align with the ICJ effect narratives about the individually disciplining and rehabilitative character of criminal justice and its general deterrent effects.